PREMIÈRES EXPÉRIENCES DE CONSOMMATION ET ADDICTION TABAGIQUE EN MILIEU SCOLAIRE IVOIRIEN - Jean-Pierre, Kouakou Bah (European Scientific Journal, ESJ, 2013)
The tobacco addiction in school of Ivory Coast is a worrying phenomenon of public health. The teenagers are with this effect most concerned. The first experiments of tobacco consumption are decisive in addictives practices. That’s why the objective of this study is to understand the living as well as subjacent social justifications in the dependency of the pupils of the cigarette. This study took place at the local secondary school of Attécoubé (Abidjan). It concerned 200 pupils smokers of the first to the final year of study. The first contact with tobacco by pupils is determined by psycho-sociological, communicational and educational factors. The psycho-sociological factor was named by 79 % of the investigated pupils among which 37 % for curiosity, 22% for snobbery, 12 % for shyness and 8 % for the parents smokers. Communicational and educational factors were brought up respectively by 15 % and 6 % of the pupils. Some places were also pointed out by the pupils as favorable to the initiation of the consumption of the cigarette. It is notably about shops (43 %), bars (34 %), nightclubs (17 %) and homes (6 %). Except these factors at the origin of the first experiments of tobacco, addictive behaviors of the pupils are lead by socials justifications. These are mainly expression of maturity (33 %), pleasure (28 %), fighting the stress (23 %) and inspiration (16 %).